Experimental investigations on wear properties of AlTiN coated 316LVM stainless steel. (2020) - Sivaprakasam, P.; Elias, G.; Maheandera Prabu, P.; Balasubramani, P.
Abstract: In this study Physical Vapor Deposition (PVD) process was used to coat the AlTiN on 316LVM stainless steel. Pin-on-disk wear tests were performed at room temperature for evaluating the specific wear rate (SWR), using variable process parameters such as load; sliding speeds and sliding distance each at three levels using face centered cubic design. Analysis of variance was employed for Specific Wear Rate (SWR). The test results revealed that main factors; interaction between load and sliding distance and quadratic effects of all three factors have significant influence on Specific Wear Rate. The minimum SWR of 0.0144 mm 3 /Nm was obtained using optimal input parameters combinations such as load 30 N, sliding speed 1.5 m/s and sliding distance 1000 m.